Learning Needs Analysis of Vocational High School`S Chemical Subjects in Mechanical Engineering Department - Hartanto, Suryo; Fordiana, Ratih (International Journal of Engineering and Technology, 2018)
Learning chemistry material is not enough to support the competence of vocational high school students because of material which is not applicable to the world of work. The purpose of this study is to reveal the scope of learning Chemistry of vocational high school at Department of Mechanical Engineering. This research used quantitative descriptive with a with a sample of 95 respondents. The research instrument used a questionnaire which has been declared valid and reliable. The data Analysis used the level of achievement of respondents and the degree of achievement. Based on the results of research, learning chemicals subject, which is needed by the vocational high school students majoring Mechanical Engineering, consists of (1) 23 basic learning competencies, (2) 61 learning materials, (3) six learning models application, (4) two learning approaches, (5) 13 learning methods, (6) five visual learning media and 4 project motion media, and (7) four aspects of cognitive assessment and four aspects of skills assessment. From these findings, it can be recommended as a reference on learning chemistry in vocational high school students majoring mechanical engineering.Â Â